Reconstruction of Skull Defects in the Middle Ages and Renaissance. (June 2015) - Missori, Paolo; Currà, Antonio; Paris, Harry S.; Peschillo, Simone; Fattapposta, Francesco; Paolini, Sergio; Domenicucci, Maurizio
In Egyptian, Greco-Roman, and Arabic medicine, the closure of a skull defect was not provided at the end of a therapeutic trepanation or in cases of bone removal. The literature from the Middle Ages and Renaissance disclosed some striking and forgotten practices. Gilbertus Anglicus (c. 1180 to c. 1250) cites the use of a piece of a cup made from wooden bowl (ciphum or mazer) or a gold sheet to cover the gap and protect the brain in these patients; this citation probably reflected a widely known folk practice. Pietro d'Argellata introduced the use of a fixed piece of dried gourd for brain protection to reconstruct a skull defect. In the late Renaissance, the negative folklore describing this outlandish practice likely led to the use of silver and lead sheets. Nevertheless, for centuries, large numbers of surgeons preferred to leave the dura mater uncovered after bone removal, and failed to apply any brain protection.